THE ROTATING SHRINK FIT WITH ELASTIC PLASTIC HUB EXHIBITING VARIABLE THICKNESS - GUVEN, U (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
Based on Tresca's yield condition, the associated flow rule and linear strain hardening, the stress distribution in the hub of a rotating shrink fit is studied. The rotating shrink fit consists of an elastic solid disk with uniform thickness and partially plasticized hub with variable thickness. It is assumed that the assembly is thin and that the variation of thickness is radial. The problem is solved in closed form.
Keywords: Mechanics